DELAY OF GERMINATION 1 mediates a conserved coat-dormancy mechanism for the temperature- and gibberellin-dependent control of seed germination - Graeber, Kai (National Academy of Sciences, 2014)
Seed germination is an important life-cycle transition because it determines subsequent plant survival and reproductive success. To detect optimal spatiotemporal conditions for germination, seeds act as sophisticated environmental sensors integrating information such as ambient temperature. Here we show that the DELAY OF GERMINATION 1 (DOG1) gene, known for providing dormancy adaptation to distinct environments, determines the optimal temperature for seed germination. By reciprocal gene-swapping experiments between Brassicaceae species we show that the DOG1-mediated dormancy mechanism is conserved. Biomechanical analyses show that this mechanism regulates the material properties of the endosperm, a seed tissue layer acting as germination barrier to control coat dormancy. We found that DOG1 inhibits the expression of gibberellin (GA)-regulated genes encoding cell-wall remodeling proteins in a temperature-dependent manner. Furthermore we demonstrate that DOG1 causes temperature-dependent alterations in the seed GA metabolism. These alterations in hormone metabolism are brought about by the temperature-dependent differential expression of genes encoding key enzymes of the GA biosynthetic pathway. These effects of DOG1 lead to a temperature-dependent control of endosperm weakening and determine the optimal temperature for germination. The conserved DOG1-mediated coat-dormancy mechanism provides a highly adaptable temperature-sensing mechanism to control the timing of germination.